Developing the Instrument of Fikih Assessment in Madrasah Aliyah - Agus Sutiyono (Nadwa: Jurnal Pendidikan Islam, 2022)
The study aimed to develop an instrument of Fikih assessment in Madrasah Aliyah (MA) that has good construct validity and at estimating the reliability of the Fikih assessment instrument in MA. This study used Research and Development (R D) Method. The subjects in this study were the students in MAN Cilacap, MAN Banyumas, and MAN Purbalingga. This study found, first, that the instrument of Fikih assessment in the Regency of Cilacap, Banyumas, and Purbalingga has not met its standards as a measurement tool. Second, the development of the Fikih instrument in the MA has used observable variables by conducting a theoretical review of the Fikih learning materials in Grade XI of Senior High School from the 2013 Curriculum. So, the researcher formulated the Fikih Instrument Items and conducted a qualitative analysis with the assistance of the Fikih experts and Evaluation and Assessment experts. Indicators with 30 items have been equal to 0.976, which means that the nine indicators of the Fikih assessment instrument provide reliable estimates for the latent variables of the Fikih instrument.